Four steps to clean hospitals: LOOK, PLAN, CLEAN and DRY. Issue 1 (September 2019) - Dancer, S.J.; Kramer, A.
Summary: Background: Now that cleaning and decontamination are recognized as integral to infection control, it is timely to examine the process in more detail. This is because cleaning practices vary widely within healthcare districts, and it is likely that both time and energy are needlessly wasted with ill-defined duties. Furthermore, inadequate cleaning will not reduce the risk of infection but may even enhance it. The process would benefit from a systematic appraisal, with each component placed within an evidence-based and ordered protocol. Methods: A literary search was performed on 'hospital cleaning', focusing on manual aspects of cleaning, pathogen reservoirs and transmission, hand hygiene, staff responsibilities and patient comfort. Results: No articles providing an evidence-based practical approach to systematic cleaning in hospitals were identified. This review therefore proposes a simple four-step guide for daily cleaning of the occupied bed space. Step 1 (LOOK) describes a visual assessment of the area to be cleaned; Step 2 (PLAN) argues why the bed space needs preparation before cleaning; Step 3 (CLEAN) covers surface cleaning/decontamination; and Step 4 (DRY) is the final stage whereby surfaces are allowed to dry. Conclusion: Given the lack of articles providing practical cleaning guidance, this review proposes a four-step protocol based on evidence if available, or justified where not. Each step is presented, discussed and risk-assessed. It is likely that a systematic cleaning process would reduce the risk of healthcare-associated infection for everyone, including outbreaks, in addition to heightened confidence in overall quality of care.